PERLINDUNGAN HUKUM TRANSAKSI BISNIS INTERNASIONAL PADA ERA PERDAGANGAN BEBAS - Wiwin Dwi Ratna; Zulvia Makka (Universitas Borneo Tarakan, 2021)
ABSTRACTThe current international business transaction activity is not difficult, with the advancement of technology, the world provides ample opportunities and opportunities for the international community to make connections between them.. International business transactions are private law studies, where in private law the law provides wider opportunities for each party to make, agree and execute the clauses they make. However, it can not be said that in order to carry out such business activities, the parties must carefully understand and understand the legal norms in the countries of the opposing parties. This will greatly affect the implementation of the agreement. For that reason it is necessary for researchers to clarify the study of legal protection of international business transactions in the era of free trade.The following issues are Legal Principles of International business transactions in the era of free trade and Legal Certainty on International Business transactions. The method used is normative legal research.This research produces the Principles of law of international business transactions can be found in the rules of international treaty law which regulates the provisions of international business transactions. The provisions of the international convention on the Contracts for the International Sale of Goods (CISG) and the UNIDROIT Principle of International Contracts of 1994 and Legal certainty in international business contracts can be seen from the legal source of international business contracts. Not surprisingly, when different business actors of citizenship conduct international business transactions, they will consent to law enforcement of one of the business actors. Keywords: Legal Protection, International Business Transactions, Free Trade